Mekanisme pembagian laba rugi pembiayaan sebagai sebuah tantangan bagi perbankan syariah di indonesia - Riyanto Wujarso (Journal of Information System, Applied, Management, Accounting and Research, 2021)
Profit and loss sharing (PLR) in Islamic banking in Indonesia faces difficulties. Contracts for financing (PLR) include mudharabah and musyarakah. Before addressing the difficulties, this analysis evaluates the mudharabah and musyarakah contracts' execution. While a musyarakah contract requires investors and entrepreneurs to provide money and labor, a mudharabah contract allows the investor to supply capital and the entrepreneur to manage the firm. In terms of return on investment, all partners share profits and losses according to the pre-agreed musyarakah ratio; however, only the financier bears the loss for the mudharabah, as the entrepreneur has lost business as a result of the scheme. This research will be discussed qualitatively and using a literature review approach. The findings indicate that there are four major impediments to PUR financing: high investment risk, difficulties in selecting the best partner, demands from consumers with a poor credit rating, and a lack of financial protection.